Development and application of microfluidic sweat detection technology in mental health monitoring - Zhao, Danni; Chen, Ran; Jiang, Shuyue; Xie, Weiwei; Zhang, Kaihuan; Zhao, Jianlong; Feng, Shilun; Bian, Shengtai (View (Beijing, China), 2025)
Mental health significantly affects individuals' thoughts and behaviors, making its monitoring crucial in high‐stakes environments like truck driving and space missions. Traditional wearable sensors often focus on physiological indicators such as heart rate, but microfluidic wearable sensors offer a promising alternative by enabling precise, quantitative analysis of sweat biomarkers. This review explores recent advancements in microfluidic wearable sensors for mental health monitoring, highlighting their ability to analyze biomarkers such as stress hormones, dopamine, and catecholamines. We discuss the development, application methods, and challenges of these sensors, as well as their future prospects in mental health monitoring. In this review, the authors emphasize the potential of microfluidic sweat detection technology in the field of mental health monitoring. The work explores the intricate relationship between psychological disorders, such as depression and anxiety, and their physiological impact, emphasizing how these conditions can influence systemic health. Furthermore, the study discusses key sweat‐associated biomarkers, including serotonin, cortisol, dopamine, glucose and lactate, which have been linked to mental health status. The review also provides an in‐depth analysis of advanced microfluidic sensor technologies, such as electrochemical sensors, nanobiosensors, enzyme‐based electrodes and colorimetric biosensors, showcasing their application in real‐time, non‐invasive mental health assessment. Additionally, this study addresses the challenges, opportunities, and future perspectives in integrating sweat biomarker detection into routine mental health diagnostics, filling a critical gap in the current literature.